PUBLICATION ETHICS: GLOBAL ISSUE, REGIONAL CHALLENGES - Behrooz Astaneh; Muhammad Irfan; Sarah Masoumi (Khyber Medical University Journal, 2014)
Publication ethics is central to academic publishing. Publication ethics is an umbrella term encompassing all ethical issues related to scientific publication, ranging from research misconducts such as duplicate publication and guest authorship to research frauds such as data fabrication and plagiarism.1-3 Contrary to the common notion, it is not only the duty of the authors to abide by the guiding principles of publication ethics but responsibility also lies with the authors; editors; reviewers; and publishers, for the appropriate handling of scientific data and should adhere to ethical guidelines of academic research.4 Since ethics is a decision making tool for any course of action and is thus the requirement for human life, it is also a fundamental aspect of research and publication because ignoring it affects the integrity of research, wastes funds and resources, and harms the research community by damaging the reputation of researchers, editors, and institutions.5,6 Moreover, the participants, the general public and the policy makers may be harmed by fraudulent published to address ethical challenges that are faced by the whole research community. 10,19,20 For authors, the organization of courses for improvement in the proficiency in English writing can be useful since the authors from non-English speaking countries often complain of their shortcomings in appropriately phrasing their expression without crossing the boundaries of publication ethics.21 Professional medical writers can also play their role to help such authors but a careful look at the conduct may be required and the internationally made guidelines need to be pragmatically implemented in this region.22-24 For Editors, there can be some solutions to the ethical dilemmas, they face.25 Train the Trainer programs, investing in editors to disseminate the knowledge related to publications and related ethical issues have been useful.26,27 A two year diploma course in Medical Journalism, running in Shiraz University of Medical Sciences is another unique and successful example of promoting awareness of Publication Ethics.28 Another opening for editors to improve their skills in all aspects of their job as an editor including their knowledge and practice of dealing with publication ethics is to create prospects of internship with reputed national and international journals.29,30 All these methods have been successfully used in the past and can be used regularly. Reviewers and publishers can also benefit from these opportunities. The Committee on Publication Ethics (COPE), a non-profit organization spearheading publication ethics was established in 1997 by a group of medical editors, is run through a council by a diverse group of editors from different countries including members from our region.31 COPE provides advice to editors and publishers on various aspects of publication ethics and provide resources including guidelines (and flowcharts) for handling different research misconducts and fraud, and educates editors through its newly launched e-learning course.13 It also funds research on publication ethics. COPE plays a key role in promoting publication ethics through its forums, seminars and congresses which are sometimes organized in collaboration with institutions in different countries.13 Such events are highly influential in promoting ethical standards among regional editors and researchers. Moreover, these events provide an opportunity for regional editors to unite in an academic setting and communicate and share their knowledge and experience regarding various challenges pertaining to publication ethics, with other colleagues. The second international congress on publication ethics will be held in Shiraz, Iran, on 4-5 December 2014, following the success of the first congress which was held in Shiraz in November 2011.32 The congress will be hosted by Shiraz University of Medical Sciences, which is Iran’s leading university in publication ethics. The theme of this year’s congress will be “Implementing Ethics in Scientific Publication” and the conference will include various topics related to publication ethics such as authorship criteria, plagiarism, data fabrication, ethical standards for editors, ethics education, etc. The congress will also include various panel discussions for enabling mutual communication and sharing of experiences between editors. It is hoped that such regional congresses would lead to higher awareness on publication ethics and future regional policymaking for the better implementation of publication ethics in regional academic setting.